(untitled) (Triyuga Academic Journal, 2025)
The dark complexion, curly hair and muscular well-proportioned bodies are identity of Santhals/Satars. They inhabit small clusters among Hindus in Jhapa, Morang and Sunsari districts in Nepal. More than 9 million Santhal live in India Dashain and Tihar festivals become vibrant due to their songs and dances.The law and order within the community is maintained with the help of village council. They are divided into a number of exogamous clan units. The most important gods of them are Thakur, Moran Baru ang Moreko. Their incantations can cure the biting of poisonous snake. Like many other communities in Nepal, they believe in life after the death.